Donor cardiac arrest and cardiopulmonary resuscitation: impact on outcomes after simultaneous pancreas–kidney transplantation – a retrospective study. (27th February 2020) - Messner, Franka; Yu, Yifan; Etra, Joanna W.; Krendl, Felix J.; Berchtold, Valeria; Bösmüller, Claudia; Brandacher, Gerald; Oberhuber, Rupert; Scheidl, Stefan; Maglione, Manuel; Öfner, Dietmar; Schneeberger, Stefan; et al.
Summary: Donor cardiac arrest and cardiopulmonary resuscitation (CACPR) has been considered critically because of concerns over hypoperfusion and mechanical trauma to the donor organs. We retrospectively analyzed 371 first simultaneous pancreas–kidney transplants performed at the Medical University of Innsbruck between 1997 and 2017. We evaluated short‐ and long‐term outcomes from recipients of organs from donors with and without a history of CACPR. A total of 63 recipients received a pancreas and kidney graft from a CACPR donor. At 1, and 5‐years, patient survival was similar with 98.3%, and 96.5% in the CACPR and 97.0%, and 90.2% in the non‐CACPR group (log rank P  = 0.652). Death‐censored pancreas graft survival was superior in the CACPR group with 98.3%, and 91.4% compared to 86.3%, and 77.4% (log rank P  = 0.028) in the non‐CACPR group, which remained statistically significant even after adjustment [aHR 0.49 (95% CI 0.24–0.98), P  = 0.044]. Similar relative risks for postoperative complications Clavien Dindo > 3a, pancreatitis, abscess, immunologic complications, delayed pancreas graft function, and relative length of stay were observed for both groups. Donors with a history of CACPR are, in the current practice, safe for transplantation. Stringent donor selection and short CPR durations may allow for outcomes surpassing those of donors without CACPR.